2018
DOI: 10.1111/bjd.16671
|View full text |Cite
|
Sign up to set email alerts
|

FACE-Q Skin Cancer Module for measuring patient-reported outcomes following facial skin cancer surgery

Abstract: The FACE-Q Skin Cancer Module meet the requirements of the Rasch model providing linearized measurement. Discriminating between patients with minimal appearance or worry impairment may be a limitation. The scales can be used for larger validation studies, clinical practice and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 42 publications
(43 reference statements)
1
74
1
Order By: Relevance
“…15,16 There is limited evidence supporting use of PROMs in NMSC populations, e.g. FACT-G, 13,16 Skin Cancer Index, 17 Facial Skin Cancer Index 18 and FACE-Q Skin Cancer Module, 19 and further evaluation of disease-specific tools is required.…”
mentioning
confidence: 99%
“…15,16 There is limited evidence supporting use of PROMs in NMSC populations, e.g. FACT-G, 13,16 Skin Cancer Index, 17 Facial Skin Cancer Index 18 and FACE-Q Skin Cancer Module, 19 and further evaluation of disease-specific tools is required.…”
mentioning
confidence: 99%
“…The characteristics of the included studies are summarized in Table 2. One study 20 was excluded even though it met the inclusion criteria because it was not clear whether the same women had been included in a larger study published by the same authors at a later date 21 . Therefore, only the later, larger study was included to prevent possible double counting of women.…”
Section: Resultsmentioning
confidence: 99%
“…None of these women was affected by further seizures or neurologic events. Sibai et al 20 presented the most historic data, including 223 women from a single institution between 1977 and 1989 21 . None of the women had recurrent seizures during a follow up period of 3–13 years.…”
Section: Resultsmentioning
confidence: 99%
“…The FACE-Q is a validated, patient-reported outcome instrument used to quantify health-related quality of life after facial surgery. 5 The Skin Cancer Module within the FACE-Q evaluates variables related to facial skin cancers. The purpose of this study was to measure patient-reported outcomes and identify factors associated with patient satisfaction after excision of facial nonmelanoma skin cancer in the veteran population.…”
Section: Patient-reported Outcomes and Factors Associated With Patienmentioning
confidence: 99%